Can we use the questionnaire SNOT-22 as a predictor for the indication of surgical treatment in chronic rhinosinusitis?, - Marambaia,Pablo Pinillos (2017)
Abstract Introduction: Chronic rhinosinusitis is a prevalent disease that has a negative impact on the lives of sufferers. SNOT-22 is considered the most appropriate questionnaire for assessing the quality of life of these patients and a very effective method of evaluating therapeutic interventions; however it is not used as a tool for decision-making. Objective: To test the hypothesis that the SNOT-22 score can predict the outcome of surgical treatment. Methods: A retrospective, longitudinal and analytical study. We evaluated the medical records of patients with chronic rhinosinusitis that completed the SNOT-22 at the time of diagnosis. All the patients were consecutively receiving care at an otolaryngology service in Salvador, Bahia from August 2011 to June 2012. The outcomes of the surgical treatment of these patients were obtained from their medical records. The initial score was compared to a group of patients who were not referred for surgery. All the patients completed and signed a consent form. Results: Of the 88 patients with chronic rhinosinusitis, 26 had evolved to surgery over the last 3 years. The groups were homogeneous regarding gender and respiratory and medication allergies. The patients of the surgical group were 44.8 + 13.8 years old and the patients of the clinical group were 38.2 + 12.5 years old (p = 0.517). The average SNOT-22 score of the case group was 49 + 19 and the average score of the control group was 49 + 27 (p = 0.927). Conclusion: The SNOT-22 was unable to predict the outcome of surgical patients with chronic rhinosinusitis.